Release of proinflammatory mediators and expression of proinflammatory adhesion molecules by endothelial progenitor cells - Zhang, Yanmin (American Physiological Society, 2009)
Cell therapy with endothelial progenitor cells (EPCs) is an emerging therapeutic option to promote angiogenesis or endothelial repair. Although the release of angiogenic paracrine factors is known to contribute to their therapeutic effect, little is known about their release of proinflammatory factors and expression of proinflammatory adhesion molecules. “Early” EPCs and “late” EPCs were isolated from human peripheral blood and their release of chemokines and thromboinflammatory mediators as well as their expression of the proinflammatory adhesion molecules was assessed at baseline and with stimulation. The effect of simvastatin on monocyte chemoattractant protein-1 (MCP-1) secretion by late EPCs from patients with vascular disease was also evaluated. All groups of EPCs released chemokines and thromboinflammatory mediators. Early EPCs primarily released thromboinflammatory mediators such as tissue factor (0.5 ± 0.1 ng/million cells, P < 0.05), whereas adult late EPCs primarily released chemokines such as MCP-1 (287 ± 98 ng/million cells, P < 0.05). Stimulation with tumor necrosis factor (TNF)-α augmented the expression of proinflammatory adhesion molecules and paracrine factors by all EPC subtypes. The release of MCP-1 by late EPCs was markedly reduced by simvastatin treatment of the cells. All EPC subtypes expressed proinflammatory paracrine factors and adhesion molecules involved in atherosclerosis. Future clinical studies should therefore not only assess the efficacy of EPCs but also monitor inflammatory activation following EPC transplantation in patients. Pharmacological modulation of EPCs before and after transplantation may represent a novel approach to improve their safety.